Retrospective Analysis of Polyethylene Oxide and Polypropylene Oxide Block Copolymers Production and Industrial Applications (Review) - E. O. Bakhrushina; V. S. Pyzhov; P. S. Sakharova; N. B. Demina; I. I. Krasnyuk (Разработка и регистрация лекарственных средств, 2024)
Introduction. Nowadays block copolymers of PEO and PPO (poloxamers, pluronics, proxanols) are among the most popular polymers in the pharmaceutical and biotechnological industries. They can be applied as effective nonionic surfactants, biological membrane stabilizers, elements of targeted delivery systems, solubilizers, as well as excipients in the technology of traditional dosage forms – gelling agents, lubricants, etc. For the past fifty years, the world's largest manufacturer of poloxamers has been the German chemical concern BASF. However, today in the Russian Federation there is a risk of defects, which defines the relevance of import substitution of this excipient.Text. The purpose of this review is to highlight the experience of production and implementation of PEO and PPO block copolymers into novel Russian scientists’ developments, comparing them with the experience of foreign research groups, which is necessary to assess the potential for import substitution. PEO and PPO block copolymers have been known in the Soviet Union since the late 60s as far as they are mentioned in textbooks of 1964 and 1973. Domestic block copolymers of PEO and PPO have been used in the oil refining industry, as well as in some branches of light industry and in the decontamination of radioactive waste. The unique domestic synthesis of PEO and PPO block copolymers was established in 1978 on the basis of the "Orgsintez" factory. Soviet poloxamers were produced under the brand name "proxanol" in a wide range of ratios of EO and PO units and molecular weights. It should be noted that today in the Russian Federation, industrial batches of the solubilizer Emuxol 268, which is close in its properties to the well-known poloxamer 188, are still produced, and block copolymers with other ratios of EO and PO units are synthesized to order.Conclusion. According to the retrospective analysis, the modern Russian industry has enough experience and resources to establish the synthesis of PEO and PPO block copolymers necessary to produce drugs and to develop innovative delivery systems and drugs. Based on the materials of the systematic review, the most complete register of known brands of PEO and PPO block copolymers synthesized over the past 50 years in our country and in the world was compiled for the first time, with a detailed description of their physicochemical properties.